Manipulating martensitic transformation and residual stress development in stress superposed incremental forming of SS304 - Elizabeth M. Mamros; Fabian Maaß; Thomas H. Gnäupel-Herold; A. Erman Tekkaya; Brad L. Kinsey; Jinjin Ha (Advances in Industrial and Manufacturing Engineering)
Stress superposition is one of the strategies used in metal deformation processes to increase the material formability, decrease the required forming forces, and create highly customized components. To investigate the effects of tensile and compressive stresses superposed to the single point incremental forming (SPIF) process, experiments and numerical simulations were conducted for a stainless steel 304 (SS304) truncated square pyramid geometry. Tensile stresses were superposed in-plane on the specimen blank by a custom hydraulic frame, and compressive stresses were incorporated via a polyurethane die. Identified parameters for a martensitic transformation kinetics model for SS304 were used in a two-step finite element approach to predict the α’-martensite volume fraction. These results were compared to experimental results measured by a Feritscope at four locations along each pyramid wall and validated by electron backscatter diffraction. The residual stresses were measured using x-ray diffraction. The parts from each incremental forming process revealed differences in the residual stresses, which impacted the final geometries, and the α’-martensite volume fraction at the four measurement locations. The evolution of the stress state, defined by the stress triaxiality and Lode angle parameter, for each process contributed to the phase transformation variance. It was found that superposing both tensile and compressive stresses to SPIF resulted in the greatest phase transformation and lowest magnitude of residual stresses near the base and the greatest overall geometrical accuracy. Stress-superposed incremental forming can be implemented to manipulate final part properties, which is ideal for applications requiring highly customized parts, e.g., biomedical trauma fixation hardware.